Preparation and Characterization of Betel Leaves (Piper betle Linn) Extract Nanoparticle with Ionic Gelation Method - Dwi Saryanti; Dian Nugraheni; Nisa Sindi Astuti (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2020)
Nanoparticles are used in drug delivery which can increase mass transfer so increase the absorption and effectiveness of the drug. Therefore, its prospect to improve antibacterial and antioxidants activities of betel leaves. The research aimed to preparation and characterization of betel leaf extract using ionic gelation technique. The formulation of nanoparticles from betel leaf extract with ionic gelation method using alginate and CaCl2 with a ratio of 2.5: 1. The characterization of the nanoparticles includes particle size analysis, zeta potential, particle morphology and determination of flavonoid content. Particle size analysis demonstrated that the betel leaf extract nanoparticles had a particle size of 243,03 ± 1,48 nm, zeta potential of -23,0 ± 0,35 mV and morphology of particle showed that a flat shape. The betle leaf exctract nanoparticle positively contained flavonoid with Rf 0.7 equivalent to quercetin. The betel leaf extract can be made nanoparticles with ionic gelation method using alginate and CaCl2.